An Activin A/BMP2 Chimera, AB204, Displays Bone‐Healing Properties Superior to Those of BMP2. (September 2014) - Yoon, Byung‐Hak; Esquivies, Luis; Ahn, Chihoon; Gray, Peter C; Ye, Sang‐kyu; Kwiatkowski, Witek; Choe, Senyon
ABSTRACT Recombinant bone morphogenetic protein 2 (rhBMP2) has been used clinically to treat bone fractures in human patients. However, the high doses of rhBMP2 required for a therapeutic response can cause undesirable side effects. Here, we demonstrate that a novel Activin A/BMP2 (AB2) chimera, AB204, promotes osteogenesis and bone healing much more potently and effectively than rhBMP2. Remarkably, 1 month of AB204 treatment completely heals tibial and calvarial defects of critical size in mice at a concentration 10‐fold lower than a dose of rhBMP2 that only partially heals the defect. We determine the structure of AB204 to 2.3 Å that reveals a distinct BMP2‐like fold in which the Activin A sequence segments confer insensitivity to the BMP2 antagonist Noggin and an affinity for the Activin/BMP type II receptor ActRII that is 100‐fold greater than that of BMP2. The structure also led to our identification of a single Activin A‐derived amino acid residue, which, when mutated to the corresponding BMP2 residue, resulted in a significant increase in the affinity of AB204 for its type I receptor BMPRIa and a further enhancement in AB204's osteogenic potency. Together, these findings demonstrate that rationally designed AB2 chimeras can provide BMP2 substitutes with enhanced potency for treating non‐union bone fractures. © 2014 American Society for Bone and Mineral Research.